Calcitonin gene-related peptide (CGRP) concentrations outside migraine attacks in peripheral blood as a potential biomarker for chronic migraine - Bhat, Showkat hassan; ASIMI, RAVOUF; shah, zaffar amin; RAINA, ADNAN FIRDOUS (Headache Medicine, 2023)
Abstract Introduction Chronic migraine is a debilitating condition that affects a significant portion of the population. Accurate diagnosis and treatment of chronic migraine remain a challenge due to the lack of objective biomarkers. Calcitonin gene-related peptide (CGRP) is a neuropeptide involved in the pathophysiology of migraine and has been proposed as a potential biomarker for migraine. Methods We measured CGRP levels in peripheral blood samples collected from 142 participants with chronic or episodic migraine and 24 healthy controls during ictal periods, i.e., outside migraine attacks. We compared CGRP levels between the three groups and assessed the correlation between CGRP levels and clinical features of chronic migraine. Conclusion Our study provides evidence that CGRP levels in peripheral blood during ictal periods may serve as a potential biomarker for chronic migraine. Further studies are needed to validate these findings and to explore the clinical utility of CGRP as a biomarker for chronic migraine.